Chinese whispers? Investigating the consistency of the language of assessment between a distance education institution, its tutors and students. (2nd September 2018) - Hills, Laura; Clarke, Anactoria; Hughes, Jonathan; Butcher, John; Shelton, Isobel; McPherson, Elaine
ABSTRACT: Ensuring the fairness of assessment is important in all areas of higher education. It is particularly so in distance education, where the communication around assessment and feedback is a principal method of supporting learning, and even more so when the students are at the entry point into higher education. This research explores the nature of the language used in explaining the purpose and process of assessment on an access programme at The Open University, UK, from the perspective of the module team, the tutors and the students. It takes a qualitative approach to examine the clarity and consistency of assessment tasks, assessment guidance and TMGs. Analysis revealed inconsistencies in the language used in relation to assessment, which has led to a revision of how assessment tasks and guidance are communicated to students and tutors.